Factors associated with severe maternal, fetuses and neonates' outcomes in a university hospital in Rio de Janeiro State - Josy Maria de Pinho da Silva; Pauline Lorena Kale; Sandra Costa Fonseca; Thamires Nantes; Nina Nogueira Alt (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to estimate the burden of parturients, fetuses and neonate's severe morbidity and mortality and investigate the association between maternal and their conceptus outcomes. Methods: retrospective cohort of 546 parturients and their conceptus in a university hospital, reference for high-risk pregnancy, in the metropolitan region II of Rio de Janeiro State from 2015 to 2017. We classified parturients according to obstetric morbidity (OM) in direct, indirect, or mixed, and their outcomes as: 1) no severity, 2) severe complication (SC), 3) critical intervention/Intensive Care Unit, and 4) greater severity -maternal near-miss (MNM) or death. We evaluated the conceptus as neonatal near-miss (NNM) and fetal and neonatal deaths. We estimated morbimortality indicators and associated factors (multinomial logistic regression). Results: OM was frequent: 29.3% indirect, 22.3% direct, and 15.8% mixed. There were eight cases of NMM, seven with direct MO. Among the conceptus: 7.5% were NNM cases and 4.4%, deaths. The risk of severe maternal outcomes was 16.8 and neonatal, 102.6/1000 live births. Mixed race, inadequate prenatal care, CG and NMM/death, were associated with NNM. Inadequate prenatal care and maternal NM/death were associated with conceptus deaths. Conclusion: even in a reference unit, sociodemographic, and health care inequalities negatively affect mothers and, consequently, their children.